HUBUNGAN LAMA PENGGUNAAN ALAT KONTRASEPSI SUNTIK 3 BULAN DMPA (DEPO MEDROXYPROGESTERONE ACETATE) DENGAN PENURUNAN LIBIDO PADA AKSEPTOR KB DI PMB HANIFATUZZAQIYA SENDURO LUMAJANG - Cicik Widayanti; Nila widya Keswara; Anik Sri Purwanti (Health and Technology Journal (HTechJ), 2024)
DMPA is a hormonal contraceptive method that is often used because of its high effectiveness. However, some users report side effects in the form of decreased libido. This study used a cross-sectional design involving 150 DMPA injectable contraceptive acceptors at several health centers in City Y. This study aims to determine the relationship between the duration of use of the 3-month DMPA (Depo Medroxy Progesterone Acetate) injectable contraceptive device and the decrease in libido in birth control acceptors in PMB Hanifatuzzaqiya Senduro Lumajang. In this research, the research design used is a quantitative research design with a cross-sectional approach, namely a type of research that emphasizes measuring or observing independent and dependent variable data only once at a time. The sampling method uses a purposive sampling method, namely samples taken according to certain characteristics of 75 respondents. The data analysis technique used is data quality testing which consists of validity and reliability tests. The results of this study indicate that there is a relationship between the duration of DMPA injection contraceptive use for 3 months and a decrease in libido in contraceptive acceptors with p-value = 0.007.